Economics of Carbon Dioxide Sequestration versus a Suite of Alternative Renewable Energy Sources for Electricity Generation in U.S., California and Illinois - Agarwal, Ramesh; Zhang, Zheming; Chusak, Lee (International Journal of Energy Economics and Policy, 2012)
An equilibrium economic model for policy evaluation related to electricity generation at national and individual state level in U.S has been developed. The model takes into account the non-renewable and renewable energy sources, demand and supply factors and environmental constraints (CO2 emissions). Economic policy analysis experiments are carried out to determine the consequences of switching the sources of electricity generation under two scenarios: in first scenario, a switch from coal to renewable sources is made for 10% of electricity generation; in the second scenario, the switch is made for 10% of electricity generation from coal to coal with clean coal technology by employing CO2 capture and sequestration (CCS). The cost of electricity generation from various non-renewable and renewable sources is different and is taken into account in the model. The consequences of this switch on supply and demand, employment, wages, and emissions are obtained from the economic model under three scenarios: (1) energy prices are fully regulated, (2) energy prices are fully adjusted with electricity supply fixed, and (3) energy prices and electricity supply both are fully adjusted. The model is applied to the states of California and Illinois, and at national level. Keywords: Carbon dioxide sequestration and mitigation; Electricity generation; Renewable energy; State-level analysis JEL Classifications: C54; C68; Q42; Q48